MACROTHEORETICAL FOUNDATIONS OF FISCAL CONSOLIDATION - I. Liutyi; D. Osetska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2016)
The article analyses the unexplored category of "fiscal consolidation". The study shows a different interpretation of the content of fiscal consolidation. It was emphasized that in today's fiscal policy in the EU aims mainly at implementing fiscal consolidation programs that provide sustainable public finances by implementing measures to limit the fiscal imbalances (especially deficit of governance and public debt). The paper analyses the fiscal consolidation program aimed at stabilizing of public finances and improve their sustainability. The research proved that fiscal rules and norms contribute to the process of fiscal consolidation.